1948
DOI: 10.1097/00006254-194810000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy and the Thyroid Gland

Abstract: The relation of thyroid activity to sex and its functions has long been recognized, but the particulars of this relationship have been subjects of endless speculation and conflicting hypotheses. Before presenting the few additional facts we have to offer, it may be well to review the facts already available and current opinions on the subject. Women are undoubtedly more susceptible than are men to all recognized functional disturbances of the thyroid gland, especially hyperactivity of the organ. The incidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
1

Year Published

1950
1950
1969
1969

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 4 publications
0
10
0
1
Order By: Relevance
“…Peters et coll. ont montré que les valeurs habituelles du PBI comprises entre 4 et 8pg/10Uml croissaient dès le second mois de la grossesse pour atteindre à terme 6,2 à 1 1,2 uni/100 ml (65). Le métabolisme basal est aussi plus élevé d'environ 20 % au cours du dernier trimestre de la grossesse et retrouve des valeurs normales vers la fin de la première semaine du post-partum.…”
Section: Conduite Obstétricaleunclassified
“…Peters et coll. ont montré que les valeurs habituelles du PBI comprises entre 4 et 8pg/10Uml croissaient dès le second mois de la grossesse pour atteindre à terme 6,2 à 1 1,2 uni/100 ml (65). Le métabolisme basal est aussi plus élevé d'environ 20 % au cours du dernier trimestre de la grossesse et retrouve des valeurs normales vers la fin de la première semaine du post-partum.…”
Section: Conduite Obstétricaleunclassified
“…and remain at these levels throughout gestation. 3 ' G - 14 The thyroid frequently enlarges and the basal oxygen consumption increases about 30 per cent during the last trimester. As not more than half this rise can be attributed to the high metabolic rate of fetal tissues, it seems likely that the alteration in thyroid activity occurs in response to hormonal changes accompanying pregnancy and is needed to promote fetal growth.…”
Section: Rationale Of Studymentioning
confidence: 99%
“…Danowski reported a trend toward a midcycle rise in the PBI, with a decrease during the postovulatory phase (134). Peters et al have shown a small decrease in the PBI from premenstrual to postmenstrual states (135). At least one investigator could determine no fluctuation in the blood iodine during the menstrual cycle (136).…”
Section: Menstruationmentioning
confidence: 99%